If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8x+5(x+4)=40+x
We move all terms to the left:
-8x+5(x+4)-(40+x)=0
We add all the numbers together, and all the variables
-8x+5(x+4)-(x+40)=0
We multiply parentheses
-8x+5x-(x+40)+20=0
We get rid of parentheses
-8x+5x-x-40+20=0
We add all the numbers together, and all the variables
-4x-20=0
We move all terms containing x to the left, all other terms to the right
-4x=20
x=20/-4
x=-5
| -2x-2(2.25)=8 | | -7+7x-3×=37 | | 7(u+3)+8=-6 | | -4(n-2)=8-4n | | 13+3=-4(8x-4) | | 23-(n-13)=6(n+5) | | -5x+x/22=-1 | | 9a-2=8a+2 | | m-9.3=13.6 | | –7r=–7−6r | | q5–-19=22 | | 16-5x=5(3x+7)+1 | | 8+2(x+2)=x+14 | | 9x-6x+10=40+x+12 | | 18=-6d-6d-6 | | q5− –19=22 | | m=-9-2m | | m=306 | | 4(n+6)=2(3-7n) | | -2c-5(c-6)=-47 | | 2(4x+8)=-41+9 | | -c+10=-10+4c-10 | | √u-5=6 | | 5x+3-(x+51)=180 | | z/9+3=-69 | | 3(r+1)-5=-3+2r | | 1+7w=-5+3w+2 | | 8=6q-8q | | 4(5x+8)=-34+26 | | z+1=-7+9z | | -2y-3=-45 | | 3c-12=6 |